ANALISIS STRATEGI PEMASARAN SYARIAH DAN DAMPAKNYA TERHADAP MINAT PEMBELIAN KONSUMEN PRODUK HALAL - Khairunnisa, Riska; Fasa, Muhammad Iqbal (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2024)
This research aims to analyze the sharia marketing strategies implemented by business actors and their impact on increasing consumer purchasing interest in halal products. In this context, sharia marketing not only focuses on profit aspects but also on ethical and moral values that align with Islamic principles. The research results show that there are four marketing mixes in Islamic marketing: product, which emphasizes the quality and halalness of the product; price, which offers competitive prices without compromising quality; place, which includes the selection of strategic locations and efficient distribution; and promotion, which utilizes social media and digital marketing techniques to reach a wider consumer base. This research method uses a descriptive qualitative approach. In addition, this research uses secondary data such as articles, journals, books, research reports, and other information sources to gather important information